A slip-based model for the size-dependent effective thermal conductivity of nanowires. (February 2018) - Calvo-Schwarzwälder, M.; Hennessy, M.G.; Torres, P.; Myers, T.G.; Alvarez, F.X.
Abstract: The heat flux across a nanowire is computed based on the Guyer-Krumhansl equation. Slip conditions with a slip length depending on both temperature and nanowire radius are introduced at the outer boundary. An explicit expression for the effective thermal conductivity is derived and compared to existing models across a given temperature range, providing excellent agreement with experimental data for Si nanowires.